2012
DOI: 10.2214/ajr.11.8192
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution CT Findings in Fibrotic Idiopathic Interstitial Pneumonias With Little Honeycombing: Serial Changes and Prognostic Implications

Abstract: Even in cases of fibrotic IIP with little honeycombing, serial CT reveals an increase in the extent of honeycombing and reticulation and a decrease in extent of GGO. Overall extent of lung fibrosis on the baseline CT examination appears predictive of survival in fibrotic IIP with little honeycombing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
64
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(71 citation statements)
references
References 20 publications
7
64
0
Order By: Relevance
“…Considering fibrotic idiopathic interstitial pneumonias (IIPs) with little honeycombing, the results from two recent publications have provided guidance on differentiating UIP from NSIP without biopsy [8,9]. In particular, UIP has been shown to be associated with increasing age, increasing reticulation and decreasing ground-glass opacities.…”
Section: Differential Diagnosis Of Atypical Ipf On Hrctmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering fibrotic idiopathic interstitial pneumonias (IIPs) with little honeycombing, the results from two recent publications have provided guidance on differentiating UIP from NSIP without biopsy [8,9]. In particular, UIP has been shown to be associated with increasing age, increasing reticulation and decreasing ground-glass opacities.…”
Section: Differential Diagnosis Of Atypical Ipf On Hrctmentioning
confidence: 99%
“…LEE et al [9] used HRCT to monitor disease progression in 154 patients (UIP: n5101; NSIP: n553) with fibrotic IIPs with little honeycombing and a histological diagnosis of a fibrotic IIP (,5% honeycombing on HRCT). The patients were followed clinically for at least 2 years.…”
Section: Using Hrct To Prognosticate Ipf and Monitor Disease Progressionmentioning
confidence: 99%
“…Though several past studies suggested that wider honeycombing is one of the HRCT findings suggesting the diagnosis of IPF [18], [19] and recent IPF guidelines might set a high value on HRCT patterns to diagnose IPF, honeycombing on HRCT may not be essential for diagnosing IPF.…”
Section: Discussionmentioning
confidence: 99%
“…typical UIP pattern at imaging) is indeed associated with an increased mortality rate as compared to patients with pathologic UIP but no honeycombing on HRCT [97,98]. The development in the extent of honeycombing on serial computed tomography is associated with shorter survival [99]. We suspect that ''waiting'' for honeycombing to diagnose IPF when early nonspecific ILD is present at HRCT may be deleterious to patients who could have undergone a diagnostic lung biopsy earlier with limited risk and be treated before lung function is too impaired.…”
Section: Honeymoon Before Honeycombingmentioning
confidence: 98%